'Mediator‐ing' messenger RNA processing. (16th December 2014) - Huang, Yan; Yao, Xiao; Wang, Gang
<x xml:space="preserve">Abstract</x> Pre‐messenger RNA (mRNA) processing, generally including capping, mRNA splicing, and cleavage‐polyadenylation, is physically and functionally associated with transcription. The reciprocal coupling between transcription and mRNA processing ensures the efficient and regulated gene expression and editing. Multiple transcription factors/cofactors and mRNA processing factors are involved in the coupling process. This review focuses on several classic examples and recent advances that enlarge our understanding of how the transcriptional factors or cofactors, especially the Mediator complex, contribute to the RNA Pol II elongation, mRNA splicing, and polyadenylation. WIREs RNA 2015, 6:257–269. doi: 10.1002/wrna.1273 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article